FRAMING IN THE NEWS HEADLINES OF THE SHIA SAMPANG CONFLICT IN THE NATIONAL AND LOCAL MASS MEDIA: A Critical Discourse Analysis - Millatuz Zakiyah; Siti Rohmah; Yulianto (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2022)
ABSTRACT This study focuses on the news frame on the news title with the theme of the Shia conflict in Sampang. This qualitative descriptive research uses a critical paradigm. Data were obtained from Tempo.co, Kompas.com, Kabar Madura and Madura Indepth in 2011-2021. The media framed the Shia Sampang conflict in the government's frame, the Shia community's frame, and the case of intolerance. Tempo and Kompas frame the government as passive in dealing with conflicts and there is forced conversion of faith, but Kabar Madura and Madura Indepth frame the opposite. Furthermore, Tempo framed the government as being involved in intimidating Shia Sampang residents into converting their beliefs; Shia residents are framed as victims who suffer and are oppressed and peace initiators, and this conflict is a Sunni-Shia conflict. Meanwhile, Kompas framed that the government threw the responsibility for resolving the Shia Sampang conflict on other government institutions and did not anticipate the conflict; the Shia people of Sampang still empowered enough to resist; and this conflict is an internal family conflict. Kabar Madura and Madura Indepth framed that the Sampang Shia conflict had been completed, facilitated by the Sampang Regional Government and the Sampang Shia residents as citizens who were not persecuted and forced to convert. ABSTRAK Penelitian ini fokus mengkaji bingkai berita pada judul berita bertemakan konflik Syiah di Sampang. Penelitian deskriptif kualitatif ini menggunakan paradigma kritis. Data diperoleh dari media massa nasional, Tempo.co dan Kompas.com dan media massa lokal Kabar Madura dan Madura Indepth pada tahun 2011—2021. Dengan memanfaatkan pendekatan wacana kritis, ditemukan bahwa media membingkai konflik Syiah Sampang dalam bingkai pemerintah, bingkai warga Syiah, dan bingkai kasus intoleransi. Tempo dan Kompas membingkai pemerintah pasif dalam menangani konflik dan terdapat pemaksaan perpindahan keyakinan, dan Kabar Madura dan Madura Indepth membingkai sebaliknya. Selanjutnya, Tempo membingkai pemerintah terlibat dalam intimidasi warga Syiah Sampang agar berpindah keyakinan; warga Syiah dibingkai sebagai korban yang menderita dan terdzolimi dan inisiator perdamaian, dan konflik ini adalah konflik Sunni-Syiah. Sementara itu, Kompas membingkai pemerintah melemparkan tanggung jawab penyelesaian konflik Syiah Sampang pada lembaga pemerintahan yang lain dan tidak mengantisipasi konflik dan warga Syiah Sampang merupakan korban yang masih cukup berdaya untuk melakukan penolakan. Konflik ini merupakan konflik internal keluarga. Kabar Madura dan Madura Indepth membingkai konflik Syiah Sampang sudah selesai difasilitasi Pemerintah Daerah Sampang dan warga Syiah Sampang sebagai warga negara yang tidak didzholimi dan dipaksa berpindah keyakinan.